Cognitive Appraisal and Stress Coping: Management Strategies Based on Gender Difference in Archery Athletes - Nada Nadia Salsabila; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Negeri Semarang, 2025)
Not a few athletes experience stress during training or competing, which can happen to male and female athletes who are influenced by internal or external factors. However, each athlete has a different way of dealing with stress to get out of the existing pressure. This study aims to analyze how gender differences can affect the cognitive appraisal process of archery athletes in dealing with stress. The quantitative descriptive method with an ex-post facto research approach was used in this study involving 23 archery athletes from Bandung City. The instruments used in the study were the Cognitive Appraisal Rating Scale (CARS) questionnaire and the Brief-COPE Inventory Scale, which were given once to respondents. After the data was obtained, data analysis was carried out using the SPSS Version 29 linear regression test. The results of the study showed that there was a significant influence of cognitive appraisal on stress coping as a management strategy based on gender differences in archery athletes. This study concludes that cognitive appraisal has a significant influence on stress coping based on gender differences between men and women in archery athletes from Bandung City. So the author suggests paying more attention to the athlete's stress condition by conducting Psychological Skills Training (PST) if the athlete is already showing signs of stress.